2022
DOI: 10.21608/ejhm.2022.252830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adipokines Among Children Infected with Some Protozoan Intestinal Parasites

Abstract: Background: Adipokines are molecules produced by adipose tissue that have involvement in the body's energy/metabolic status and inflammation. It has recently been shown that there is a relationship between these molecules and infection with some intestinal parasites. Objectives: The current research aimed to assess the effect of Cryptosporidium and Giardia lamblia on adipokines. Patients and methods: This research was conducted in Baghdad from October 2021 to March 2022. The study included 56 children of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
1
1
Order By: Relevance
“…This disagrees with other studies [35][36][37] that observed a significant negative correlation between plasma adiponectin levels and BMI. Additionally, our findings disagree with Lina et al [38], who noted a non-significant correlation between adiponectin and BMI.…”
Section: Discussioncontrasting
confidence: 99%
“…This disagrees with other studies [35][36][37] that observed a significant negative correlation between plasma adiponectin levels and BMI. Additionally, our findings disagree with Lina et al [38], who noted a non-significant correlation between adiponectin and BMI.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the study showed that the highest infection rate with the Entamoeba histolytica parasite in Babylon hospitals was in the month of July, amounting to 25.5%, while the highest infection rate in Karbala city hospitals was in the month of May, amounting to 42.3% While the lowest percentage was in the months of December and November and reached ( 9.9% , 9.3% ) in hospitals in Babylon and Karbala, respectively. It agreed with the results of [23] study, and [24] as the percentage was highest in the month of July, and May, when it reached 31.1 % and 4.66% respectively he lowest infection rate was with the [24] study, which was in December and reached 3.87%…”
Section: Figure ( 1 ) : the Rates Of Infection With The Entamoeba His...supporting
confidence: 88%
“…A diseases formation of these parasite is related with effect of trophozoite attachment to upper portion of small intestine, and their protolytic enzymes (cysteine proteases and glycosidases) (10,11). This increases rate of enterocyte apoptosis, loss of barrier function, leading to lymphocyte-mediated microvillus shortening and reduction of absorptive surface area, ultimately are responsible for mal-digestion and malabsorption of nutrients (12)(13)(14). In acute clinical stages, are almost clinically overlapping that characterized by fever, watery diarrhea and other intestinal disorders (6,15).…”
Section: Introductionmentioning
confidence: 99%